IMPACT OF COGNITIVE COMPETENCIES, EMOTIONAL INTELLIGENCE AND LOCUS OF CONTROL ON THE PERFORMANCE OF ASPIRING MANAGERS - Mayur, Shruthi J (Journal of Contemporary Research in Management (JCRM), 2017)
The Indian industry has voiced its concern that most management graduates are unemployable because of skill deficiency. The skills they look for are well articulated and in general conforms to the generic skills postulated in Human Capital Theory. The intake into the management program is based on the Management Aptitude TestÂ  (MAT) Score and the Group Discussion and Personal Interview (GDPI) score. These are supposed to measure the potential of the individual to learn the genericÂ  and technical (managerial) skills. If MAT and GDPI scores indeed measures this potential, subject to an appropriate process, they would possess the generic skills. Since this is not so the problem could lie either with the intake measure or with the process. This study is about the appropriateness of the intake measure.